PERANCANGAN KEMASAN BUAH SALAK SEGAR DALAM BENTUK TANDAN (SALAK PONDOH BANJARNEGARA, JAWA TENGAH) - Rafika Ratik Srimurni, Emmy Darmawati, dan Indah Yuliasih (Jurnal Teknologi Industri Pertanian, 2018)
The bunches snake fruit has an unique form that become a typical appeal for the customerand also improve the marketing that rarely available, because of the limited form of packaging. It needs to be supported by primary and secondary packaging. The aim of this research was to obtain the primary and secondary packaging designs of the bunches snake fruit with the additional of the net foam. The corrugated cardboard C flute (RSC type) and BC flute (PTD type) were used as the material for the primary and secondary packagings. The ventilation holes was given for air circulation. The steps of this research were to design the dimension of primary and secondary packaging for the bunches snake fruit,to measure the compressive strength and maximum number of packaging stacks, and to analyze the efficiency of packaging arragement on the pallet and in a pickup. The dimensions of primary packaging was15.98 × 15.98 × 18.48 cm that has a maximum compressive strength of 65 kgf to stacks 23-43 packs. The dimensions of secondary packaging were50.04 × 34.06 × 28.54 cm (body), and 52.84 × 36.86 × 14.97 cm (cover) that has the maximum compressive strength of 132.2 kgf was capable to hold 3-4 stacks. The dimensions of secondarypackaging were included in good fit efficiency in pick-up and average fit on pallet (size 1200 × 800 and 1140 × 1140 mm), so it can supplied for local and export distribution needs to some European contries, Singapore, and China.Keywords: snake fruit, bunch, packaging design, corrugated box, transportation packaging